The forbidden stone / A secret past can destroy the future - Abbott, Tony, 1952- (The Copernicus legacy ;, 2014)
"Wade, Lily, Darrell, and Becca fly from Texas to Germany for the funeral of an old family friend. But instead of just paying their respects, they wind up on a dangerous, mind-blowing quest to unlock an ancient, guarded secret that could destroy the fate of the world"--